EATING DISORDERS CAN LEAD TO ACUTE GASTRIC DILATATION, ISCHEMIC NECROSIS, AND RUPTURE - A CASE REPORT AND LITERATURE REVIEW (CAHIERS MAGELLANES-NS, 2024)
Introduction Eating disorders are disturbances of eating impairing health or psychosocial functioning. These disorders can lead to potentially lethal complications like acute gastric dilatation, necrosis, and perforation. There are only 75 cases identified in the literature up to the beginning of 2022 and this is the 1st reported case in Saudi Arabia. Case presentationA 19-year-old Saudi female known case of anorexia nervosa. She presented to the Emergency room c /of abdominal pain for 12 hours after ingesting a heavy meal. The patient became unstable, an exploratory laparotomy was done. It revealed frank spillage of several liters of partially digested food. During the evaluation of the stomach, there was a large area of necrosis and perforation extending along the proximal greater curvature. damage control surgery was performed, which required a total gastrectomy, cervical esophagectomy, and feeding jejunostomy. The patient expired the next day with septic shockDiscussion and conclusion Acute gastric dilation has potentially fatal consequences, so a low threshold of suspicion is required for any patient presenting with severe abdominal pain following an episode of binge eating. The treatment should probably be before the occurrence of any irreversible damage.